Two to tangle: financial development, political instability and economic growth in Argentina (1896 - 2000) - Nauro F. Campos; Menelaos G. Karanasos; Bin Tan (Institute for the Study of Labor (IZA), 2008)
This paper investigates the effects of financial development and political instability on economic growth in a power-ARCH framework with data for Argentina from 1896 to 2000. Our findings suggest that (i) informal or unanticipated political instability (e.g., guerrilla warfare) has a direct negative impact on growth; (ii) formal or anticipated instability (e.g., cabinet changes) has an indirect (through volatility) impact on growth; (iii) the effect of financial development is positive and, surprisingly, not via volatility; (iv) the informal instability effects are much larger in the short- than in the long-run; and (v) the impact of financial development on economic growth is negative in the short- but positive in the long-run.
urn:nbn:de:101:1-2008112680
Keywords: C14; 330; Economic growth; financial development; volatility; political instability; power-ARCH; Finanzmarkt; Politische Stabilität; Politische Unruhen; Wirtschaftswachstum; Wirtschaftsgeschichte; Argentinien